Heat-Mass Transfer of Nanofluid in Lid-Driven Enclosure under three Convective Modes - Rahman, MS; Nasrin, R; Hoque, MI (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Heat is a form of energy which transfers between bodies which are kept under thermal interactions. When a temperature difference occurs between two bodies or a body with its surroundings, heat transfer occurs. Heat transfer occurs in three modes. Three modes of heat transfer are conduction, convection and radiation. Convection is a very important phenomenon in heat transfer applications and it occurs due to two different gradients, such as, temperature and concentration. This paper reports a numerical study on forced-mixed-natural convections within a lid-driven square enclosure, filled with a mixture of water and 2% concentrated Cu nanoparticles. It is assumed that the temperature difference driving the convection comes from the side moving walls, when both horizontal walls are kept insulated. In order to solve general coupled equations, a code based on the Galerkin's finite element method is used. To make clear the effect of using nanofluid on heat and mass transfers inside the enclosure, a wide range of the Richardson number, taken from 0.1 to 10 is studied. A fair degree of precision can be found between the present and previously published works. The phenomenon is analyzed through streamlines, isotherm and iso-concentration plots, with special attention to the Nusselt number and Sherwood number. The larger heat and mass transfer rates can be achieved with nanofluid than the base fluid for all conditions at Richardson number, Ri = 0.1 to 10. It has been found that the heat and mass transfer rate increase approximately 6% for water with the increase of Ri = 0.1 to 10, whereas these increase about 34% for nanofluid. GANIT J. Bangladesh Math. Soc.Vol. 38 (2018) 73-83